Legumes Modulate Allocation to Rhizobial Nitrogen Fixation in Response to Factorial Light and Nitrogen Manipulation - Friel, Colleen A.; Friesen, Maren L. (Frontiers in Plant Science, 2019)
The costs and benefits that define gain from trade in resource mutualisms depend on resource availability. Optimal partitioning theory predicts that allocation to direct uptake versus trade will be determined by both the relative benefit of the resource acquired through trade, and the relative cost of the resource being traded away. While the costs and benefits of carbon:nitrogen exchange in the legume-rhizobia symbiosis have been examined in depth with regards to mineral nitrogen availability, the effects of varying carbon costs are rarely considered. Using a growth chamber experiment, we measured plant growth and symbiosis investment in the model legume Medicago truncatula and its symbiont Ensifer medicae across varying nitrogen and light environments. We demonstrate that plants modulate their allocation to roots and nodules as their return on investment varies according to external nitrogen and carbon availability. We find empirical evidence that plant allocation to nodules responds to carbon availability, but that this depends upon the nitrogen environment. In particular, at low nitrogen–where rhizobia provided the majority of nitrogen for plant growth–relative nodule allocation increased when carbon limitation was alleviated with high light levels. Legume’s context-dependent modulation of resource allocation to rhizobia thus prevents this interaction from becoming parasitic even in low-light, high-nitrogen environments where carbon is costly and nitrogen is readily available.